Sistem Pendukung Keputusan Pemilihan Pelanggan Terbaik Menggunakan Metode MOORA Studi Kasus CV Sinar Indah Sejahtera - Sahroni; Anief Fauzan Rozi (Universitas Mercu Buana Yogyakarta, 2022)
CV Sinar Indah Sejahtera is one of the businesses engaged in trading/marketing where CV Sinar Prosperity acts as a provider and also as a distributor of basic necessities. For basic necessities, including rice, sugar, salt, peanuts, green beans, and also various other basic necessities. In order to improve the quality of sales and to establish communication and trust in consumers, CV Sinar Indah Sejahtera has the initiative to provide discounts/rebates to the best customers owned by CV Sinar Indah Sejahtera. Based on the above ideas, therefore we need a system that can process customer data which produces the best customer decision output, CV Sinar Indah Sejahtera. One of the roles of a Decision Support System (DSS) is to manage data using certain calculation methods which will produce a recommendation for a decision sequence. In this case CV Sinar Indah Sejahtera will use a decision support system using the MOORA calculation method to determine the best customer. From the test results that have been carried out from 5 alternative data, the best results are Mrs. Afui with a value of 35.9678 and second place is Aseng with a value of 29.5007 and the percentage of system performance is 80% which has been explained in the sub-chapter 4.2.4.2 Validation of Ranking Results with Facts.